N‐acety‐b‐D‐glucosaminidase: A potential biomarker for early detection of acute kidney injury in acute chest pain - Kaufmann, Manuel; Schlossbauer, Michael; Hubauer, Ute; Stadler, Stefan; Fischer, Marcus; Wallner, Stefan; Hupf, Julian; Zimmermann, Markus; Orso, Evelyn; Zeman, Florian; Luchner, Andreas; Maier, Lars; et al. (Nephrology (Carlton, Vic.), 2020)
Aim Acute kidney injury (AKI) is often underdiagnosed due to several limitations of the renal marker creatinine. Tubular urinary biomarkers may substantially contribute to diagnose AKI early. For early detection of AKI, we evaluated for the first time N‐acetyl‐β‐d‐glucosaminidase (NAG), Kidney‐injury‐molecule‐1 (KIM‐1) and neutrophil gelatinase‐associated lipocalin (NGAL) in acute chest pain. Methods We included 402 chest pain patients aged 18 to 95 years seen in the emergency department. From 311 subjects, blood and urine samples were collected. Results Thirty‐three patients developed an AKI and showed a significant increase in all three tubular markers compared to patients without AKI (each P < .001). According to receiver operating characteristic (ROC) analysis, combining NAG and creatinine showed a significantly increased area under the curve (AUC) compared to creatinine alone (AUC: 0.75 vs 0.87; P < .001). KIM‐1, NGAL and cystatin C showed no significant differences in AUC compared to creatinine. In 120 individuals with blood and urine sampling before contrast media exposure, ROC analysis showed a significantly improved diagnostic performance for the combination of both (AUC: 0.83 vs creatinine AUC: 0.66; P = .004). AKI occurrence showed no dependency from CM volume. NAG presented as an independent AKI predictor beside creatinine, age, the diagnosis of myocardial infarction and mean arterial pressure. Regarding the prognostic value for renal replacement therapy, the combination of NAG and creatinine showed a significantly lager AUC than creatinine (AUC: 0.95 vs AUC: 0.85; P < .001). Conclusion NAG presented as a promising marker of impending AKI and the necessity of renal replacement therapy. Summary at a glance This study reveals that N‐acetyl‐β‐d‐glucosaminidase (NAG) is a promising marker to identify patients at high risk for acute kidney injury even before significant increase in serum creatinine. In addition, the combination of NAG and creatinine has higher prognostic value for renal replacement therapy than creatinine alone.